2006
DOI: 10.1111/j.1365-2966.2006.10801.x
|View full text |Cite
|
Sign up to set email alerts
|

Supermassive black hole formation during the assembly of pre-galactic discs

Abstract: In this paper, we discuss the evolution of gravitationally unstable pre‐galactic discs that result from the collapse of haloes at high redshift z≈ 10 or so, which have not yet been enriched by metals. In cases where molecular hydrogen formation is suppressed, the discs are maintained at a temperature of a few thousand Kelvin. However, when molecular hydrogen is present, cooling can proceed down to a few hundred Kelvin. Analogous to the case of the larger‐scale protogalactic discs, we assume that the evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
513
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(528 citation statements)
references
References 41 publications
12
513
2
1
Order By: Relevance
“…The UV specific intensity in the LW band, Jν = J * 21 × 10 −21 erg s −1 cm −2 Hz −1 sr −1 , required for quenching is somewhat uncertain, but lies in the range J * 21 = 0.1 − 1 (see, e.g., Machacek et al 2001 andFialkov et al 2013). When instead primordial, atomic-cooling halos (Tvir > 10 4 K) are exposed to a LW flux of even higher intensity, Jν > J • ν (Loeb & Rasio 1994;Eisenstein & Loeb 1995;Begelman et al 2006;Lodato & Natarajan 2006;Regan & Haehnelt 2009;Shang et al 2010;Johnson et al 2012;Agarwal et al 2012;Latif et al 2013a) the destruction of H2 molecules allows a rapid, isothermal collapse, initially driven by H I Lyα line cooling, later replaced by two-photon emission. The precise value of J • ν depends on several factors, but there is a general consensus that it should fall in the range 30 < J • 21 < 1000, depending on the spectrum of the sources (Sugimura et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The UV specific intensity in the LW band, Jν = J * 21 × 10 −21 erg s −1 cm −2 Hz −1 sr −1 , required for quenching is somewhat uncertain, but lies in the range J * 21 = 0.1 − 1 (see, e.g., Machacek et al 2001 andFialkov et al 2013). When instead primordial, atomic-cooling halos (Tvir > 10 4 K) are exposed to a LW flux of even higher intensity, Jν > J • ν (Loeb & Rasio 1994;Eisenstein & Loeb 1995;Begelman et al 2006;Lodato & Natarajan 2006;Regan & Haehnelt 2009;Shang et al 2010;Johnson et al 2012;Agarwal et al 2012;Latif et al 2013a) the destruction of H2 molecules allows a rapid, isothermal collapse, initially driven by H I Lyα line cooling, later replaced by two-photon emission. The precise value of J • ν depends on several factors, but there is a general consensus that it should fall in the range 30 < J • 21 < 1000, depending on the spectrum of the sources (Sugimura et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More recent theoretical work has called into question whether the high-redshift seeds of SBHs were truly this massive. While some maintain that massive central concentrations of gas at the centers of pre-galactic disks can directly collapse into ∼ 10 5 M ⊙ SBH seeds [31], others argue that metal-free gas will fragment into Population III stars with characteristic masses 100M ⊙ [32]. Volonteri, Haardt, and Madau [33], also using the Press-Schechter formalism to estimate halo mass functions and merger rates, showed that 150 M ⊙ seeds occupying 3.5 − 4σ overdensities at redshift z = 20 could grow into SBHs that would reproduce both the quasar luminosity function at 1 ≤ z ≤ 5 and the observed local M BH −σ relation [3] between SBH mass and galaxy velocity dispersion.…”
Section: A Mass Ratiomentioning
confidence: 99%
“…One is remnant BHs of massive Population III (Pop III) stars with ∼ 100 M (Madau & Rees 2001;Haiman & Loeb 2001;Schneider et al 2002;Islam, Taylor & Silk 2003;Volonteri, Haardt & Madau 2003;Tanaka & Haiman 2009). Second, the socalled direct collapse model (Loeb & Rasio 1994;Oh & Haiman 2002;Bromm & Loeb 2003;Begelman, Volonteri & Rees 2006;Lodato & Natarajan 2006;Shang, Bryan & 2014). When the BH is fed by sufficiently strong gas flows, and the emergent luminosity increases, radiative feedback is likely to affect gas dynamics.…”
Section: Introductionmentioning
confidence: 99%